Detection of a novel porcine circovirus‐like agent in aborted pig foetuses. Issue 5 (8th March 2018) - Wen, L.; Mao, A.; Zhu, X.; Xie, J.; He, K.
Summary: A large outbreak of swine abortion, which began in January 2017, is ongoing in Jiangsu and Anhui provinces, China. We identified a new porcine circovirus‐like agent, designated P4, in the aborted foetuses from several of these cases of swine reproductive failure. PCR and qRT‐PCR analyses confirmed that other common abortogenic agents were not present in these animals. P4 contains a 710‐nucleotide circular viral genome, and all strains examined in this study were closely related to the dominant genotype of porcine circovirus type 2. Further studies, such as in vivo analyses, are needed to confirm P4 as the aetiological agent.